DIETARY INTERVENTIONS AND THEIR EFFECTIVENESS IN THE TREATMENT OF ENDOMETRIOSIS - NARRATIVE REVIEW - Natalia Alicja Kwaśniewska; Szymon Stupnicki; Mikołaj Zakryś; Katarzyna Anna Zakryś; Mateusz Szot; Aleksandra Oparcik; Jakub Tarczykowski; Michał Grzegorz Woźniak (International Journal of Innovative Technologies in Social Science, 2026)
Endometriosis is a chronic and complex systematic condition that impacts approximately 10% of women of reproductive age worldwide. Available literature has shown that selected diets have positive effects on the development and course of endometriosis. This review aimed to present current data on various dietary interventions and their effectiveness in reducing endometriosis symptoms and risk. The 19 included original studies were analyzed and included in the review. Most of the studies reported a positive effect on endometriosis-related symptoms. The Mediterranean diet was reported as a plausible adjunct therapy for symptom management without difficulty in adherence. More restrictive diet regimens, such as the Low-FODMAP diet and gluten-free diet, were reported to alleviate endometriosis-related symptoms, however adherence proved to be more difficult. Further well-designed randomized controlled trials are crucial to determine the short-term and long-term effectiveness and safety of different dietary interventions.